Congenital Zika virus syndrome...what else? Two case reports of severe combined fetal pathologies - Manon Vouga; David Baud; Eugénie Jolivet; Fatiha Najioullah; Alice Monthieux; Bruno Schaub (BMC, 2018)
Abstract Background Zika virus (ZIKV) has recently emerged as a teratogenic infectious agent associated with severe fetal cerebral anomalies. Other microorganisms (TORCH agents) as well as genetic disorders and toxic agents may lead to similar anomalies. In case of fetal anomalies, the exact etiology might be difficult to establish, especially in ZIKV endemic countries. As the risks associated with maternal infection remain unclear adequate parental counseling is difficult. Case presentation We present two cases of severe fetal pathologies managed in our multidisciplinary center during the ZIKV outbreak in Martinique, a French Caribbean Island. Both fetuses had congenital ZIKV infection confirmed by RT-PCR. While one case presented with significant cerebral anomalies, the other one presented with hydrops fetalis. A complete analysis revealed that the fetal lesions observed resulted from a combination of ZIKV congenital infection and a genetic disorder (trisomy 18) in case 1 or congenital Parvovirus B19 infection in case 2. Conclusions We highlight the difficulties related to adequate diagnosis in case of suspected ZIKV congenital syndrome. Additional factors may contribute to or cause fetal pathology, even in the presence of a confirmed ZIKV fetal infection. An exact diagnosis is mandatory to draw definitive conclusions. We further emphasize that, similarly to other congenital infections, it is very likely that not all infected fetuses will become symptomatic.